(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
An illustration published in October 1971 on the front page of Iran Free Press, an overseas-based opposition publication, depicts Shah Mohammad Reza Pahlavi cheering elegant foreigners at a party . On the table chicken and pork, whereas in Islam pork is regarded as unclean and its consumption is forbidden. In the caption below the illustration, the Shah says: «Here’s to us, forget about those beggars outside, they’re just Iranians» .